The Effectiveness of Using Animated Films on Improving Students’ Writing Skill of Narrative Text of The Eighth Grade of Mts Al-Hadi Girikusumo - Irwan Adi Putra (Universitas PGRI Semarang, 2015)
This final project was based on research which attempted to examine the Effectiveness of Using Animated Films in Improving Students’ Writing Skill of Narrative Text. The main objectives of this research was to find out whether the use of animated film can be effective in teaching writing narrative text to the students of Mts Al-Hadi Girikusumo Mranggen. This research was a quasi-experimental research. The population of the final project was limited of the eighth grade students of MTs Al-Hadi Girikusumo Mranggen in the Academic year 2014/2015 in the second semester. There were 40 students as the sample. They were divided into two groups and they did three types of activities; pre-test, treatment, and post-test. The data were collected through a writing test. The analytical score based on the elements of writing processed the data analysis. The result of t-test in post-test shows a significant difference in the achievement between two groups. From the calculation enclosed the mean of post-test of the experimental group was higher than the control group that was 60.5>39.6, it means that the achievement of the experimental group was higher than the control group. Based on the data analysis, the researcher concludes that the strategy of using animated films in teaching narrative text writing seemed to be applicable for the eighth grade students of MTs AL-Hadi Girikusumo Mranggen in academic year 2014/2015, since the strategies also help students to solve their problems in writing a text. The researcher suggests that English teacher use this method as an additional method to anticipate students’ boredom during writing class. In additional, this method improved students’ fluency in writing English because it was used to write the history.